A mechanical model for concrete slabs subjected to combined punching shear and in-plane tensile forces. (15th March 2021) - Deifalla, A.
Highlights: An extensive review for six decades of experimental punching shear testing of slabs under axial tension. The effect of various parameter on punching shear behavior of slabs under axial tension. A physically sound, simple, and accurate model for punching shear and axial tension is proposed. Abstract: Punching shear failure of reinforced concrete (RC) slabs is a sudden one, which has catastrophic outcomes. Flat slabs with large restrained dimensions, may be subjected to in-plane tensile forces due to thermal or earthquake loading. With the growing demand for optimum design and reduced safety factors, neglecting the effect of these forces on the punching shear design is not an option. Over the last 6 decades, research efforts have explained many issues regarding punching shear behavior of RC slabs subjected to in-plane compression loading. However, hand full of research investigations were directed towards studying those subjected to in-plane tensile forces. Even those limited studies were mostly experimental testing and comparison with design codes. The purpose of this study is to develop a physically sound mechanical model for concrete slabs under combined punching shear and in-plane tensile forces. Literature review for the experimental investigations, design codes and mechanical models for slabs under punching shear and in-plane tensile forces was conducted. A punching shear mechanical model, which explains the experimentally observed behavior of RC slabs under combined in-plane tensile forces and punching shear was developed and proposed. It captured the effect of various parameters in a physically sound manner as well as being consistent with the well-established critical shear crack theory.